IMPLEMENTASI METODE INQUIRY BASED LEARNING DALAM MENINGKATKAN CREATIVE THINKING SKILLS - Abditama Srifitriani; Swiejti Maghfira Regita; Muhammad Alfarizqi Nizamuddin Ghiffar (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2022)
The purpose of this study was to test the effectiveness of the 21st century form of learning with the Inquiry based learning method to improve students' creative thinking skills. Inquiry based learning method is a teaching method in which teachers involve students in the learning process through the use of ways of asking questions, problem solving activities, and critical thinking so that with this method students can think creatively to find new relationships between various things, find a new solution of something, find a new system, find a lot of new artistic, and so on. This is important due to the lack of learning methods about creative thinking skills in schools and the importance of these skills to students, so that they can solve problems in certain situations because of doubts or problems that arise. The type of research used is classroom action research (CAR) with a research design that is Guidance and Counseling Action Research (PTBK). The subjects in this study were 38 students from high school in Yogyakarta with data collection instruments, namely through observation and tests. The data in this study were collected in quantitative form (numbers) so that they could be analyzed statistically. The use of statistical data analysis in this study used the t-test formula. This research was carried out through several cycles in the form of 2 cycles. The first cycle (Planning and Action) and the second cycle (Observing and Reflecting) which aims to improve creative thinking skills through actions that are directed and guided according to the planned method. Based on the results of data analysis, it is known that the Inquiry based learning technique can improve the creative thinking skills of 38 high school students in Yogyakarta, which is seen from the t-count value is higher than before the action. The implementation of these actions is in the form of 2 cycle activities. Materials in the form of problem solving cases of bullying, brawls, and gadgets directed by researchers can be solved with pure thoughts from students using their own ways. So with the Inquiry based learning method, it is hoped that educators can apply it consistently to students who have problems or are weak in creative thinking.